Perfiles - School of Arts and Sciences (Tufts Archival Research Center, 2022)
Perfiles is an inter-disciplinary, multi-language journal that includes essays, poems, fiction, and photographs by students, faculty, and community members, with a focus on Latin America and the Caribbean.